The Relevance of the Philosophy of Language to Pedagogical Approaches in Arabic Language Education - Khotijah Khotijah; Irfan Salim; Irfan Hania (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study examines how philosophy of language—specifically theories of meaning, signs, and speech acts—can enrich Arabic pedagogy by providing a context-sensitive epistemological foundation for contemporary instruction. Design/methods/approach – This research employs a qualitative conceptual approach using document-based analysis. Primary and secondary literature on philosophy of language, linguistic theory, and Arabic language pedagogy were identified, selected, and analyzed through thematic content analysis. The process involved categorizing theoretical constructs, mapping their pedagogical relevance, and synthesizing them into an integrated instructional model. The analysis relies on theoretical triangulation to ensure conceptual rigor and coherence. Findings – The study reveals that philosophical theories of meaning, semiotic representation, and speech acts provide a robust framework for addressing the limitations of structural and communicative methods traditionally used in Arabic language classrooms. The integration of these theories highlights the centrality of context, intention, and social function in meaning-making and demonstrates that effective Arabic instruction requires more than grammatical accuracy or fluency. The proposed synthesis model incorporates illocutionary functions, multimodal signs, and interpretative practices to help learners construct deeper semantic, pragmatic, and cultural understanding. Research implications – This research mandates integrating philosophical theories into Arabic pedagogy to enhance learners' pragmatic competence, cultural interpretation, and context-driven meaning-making beyond mere grammatical accuracy.